(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2020)
Interviewing is a usual research method in qualitative research which is widely used in pedagogy as well. Yet, interviewing very young children is rather rare as it carries special difficulties and researchers find it better not to overcomplicate the research process for the sake of potentially not useful material. While this might be true, it is worth focussing on the hardships and special features of this research technique, too. Therefore, the study shows the difference between interviewing children and adults, and at the same time, it also deals with a timely topic, multilingualism, which the present study will examine from the point of view of the kindergarteners. The originality of the study lies not in conducting interviews as a part of qualitative research but in the intention according to which the author wants to concentrate on this method, i.e. interviewing very young children (between 3 and 6) showing that it is a special job which demands more attention in educational linguistics.